2023
DOI: 10.22541/au.167570558.82410707/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron Deficiency Anemia Detection using Machine Learning Models: A Comparative Study of Fingernails, Palm and Conjunctiva of the Eye Images.

Abstract: Anemia is one of the global public health challenges that particularly affect children and pregnant women. A study by WHO indicates that 42% of children below 6 years and 40% of pregnant women worldwide are anemic. This affects the world’s total population by 33%, due to the cause of iron deficiency. The non-invasive technique, such as the use of machine learning algorithms, is one of the methods used in the diagnosing or detection of clinical diseases, which anemia detection cannot be overlooked in recent day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Their study showed that Random Forest worked best with accuracy of 86.4%. In the research work [11], ML algorithms were used to determine if conjunctiva of eyes, palpable palm or color of fingernails is more accurate to detect anemia among children. Their study showed that CNN has worked better, being 99.12% accurate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study showed that Random Forest worked best with accuracy of 86.4%. In the research work [11], ML algorithms were used to determine if conjunctiva of eyes, palpable palm or color of fingernails is more accurate to detect anemia among children. Their study showed that CNN has worked better, being 99.12% accurate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to the conjunctiva and fundus, the region of ngernails appears to be the most accessible melanin-free tissue site, hence, recent works [20][21][22][23][24][25][26][27] have utilized RGB-imaging of ngernails for assessing Hb level. The work of Mannino et al demonstrated a root mean squared error of ~12 g/L and detection of Hb level lower than 125 g/L with a sensitivity and speci city values of 0.92 and 0.76, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Mannino et al demonstrated a root mean squared error of ~12 g/L and detection of Hb level lower than 125 g/L with a sensitivity and speci city values of 0.92 and 0.76, respectively. Typically, further studies report similar or even higher regression and classi cation quality scores [21][22][23][24][25][26][27], which, however, are not always con rmed in independent prospective studies. For example, RGB-imaging method applied for estimation of low Hb level demonstrated sensitivity and speci city at the level of 0.4-0.6 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia happens either when the body's red blood cell production declines or the cells' structural integrity is compromised [ 3 ]. Anaemia can also appear when the haemoglobin level in the red blood cells drops below the typical threshold as a result of increases in red blood cell oxidation, blood loss, defective cells, or a reduction in the quantity of red blood cells [ 1 ].…”
Section: Introductionmentioning
confidence: 99%